MINIRISET Increased adequacy of breast milk production in postpartum mothers using a decoction of sweet potato leaves in the Work Area of Puskesmas I Kesesi I Pekalongan Regency - Sri Utami Subagio (Jurnal Kebidanan, 2019)
Background of Mother's Milk (ASI) is the best and most ideal food for babies, because breast milk contains all the nutrients needed in the right amount and consideration but there was a decrease in exclusive ASI coverage in Pekalongan Regency in 2016 amounting to 40.73% while in 2017 amounted to 38.36% decoction of sweet potato leaves as one of the nutritional alternatives to increase milk production, decoction of sweet potato leaves has lactogogum content as an enhancer of prolactin hormone and increases milk production. Objective: to determine the effect of cassava leaf decoction on increasing milk production. Method: This research is a miniriset with descriptive research type. Samples of 2 postpartum mothers who will be assessed for the adequacy of breast milk production before and after giving 200 grams of sweet potato leaves daily for 7 days using an observation sheet. Results and Discussion: childbirth mothers who have little breast milk production after being treated with water for decoction of sweet potato leaves for 7 days experience an increase in breast milk production based on 6 aspects that have been assessed, namely based on the mother's condition about the condition of ASI production and the condition of babies who have been given ASI. Conclusions and suggestions: there is an effect of giving cassava leaf decoction for 7 days to the adequacy of breast milk so that the midwife can advise postpartum mothers to make a decoction of sweet potato leaves as an alternative to cheap and easy to obtain foods that can increase breast milk productionKeywords: decoction of sweet potato leaves; post partum mother; ASI production